Nucleotide sequence of the envelope gene of Friend murine leukemia virus. - Koch, W (1983)
The envelope gene of the helper-independent, highly leukemogenic virus Friend murine leukemia virus was sequenced by using a molecular clone of a Friend murine leukemia provirus. The deduced amino acid sequences of the envelope proteins gp70 and p15env were homologous to the sequences of Moloney murine leukemia virus (86%) and Akv (76%). However, a stretch of about 40 amino acid residues near the middle of gp70 was dissimilar in Friend and Moloney murine leukemia viruses and Akv. In this type-specific region the gp70s of all three viruses contained more than 30% proline residues, giving this sequence a very rigid conformation. We suggest that this rigid and highly variable region of gp70 participates in infection by recognition of cell surface receptors and, in addition, might contribute to the different oncogenic spectra of murine leukemia viruses.